Desenvolvimento de uma metodologia de pré-concentração e determinação de Ni(II) em matrizes alcoólicas utilizando cascas de mexerica (Citrus reticulata Blanco) como bioadsorvente - Ribeiro, Gabriela da Costa (2011)
This work describes the development of analytical methodology for Ni(II) determination in ethanol fuel applying also to other alcoholic matrices (whisky and sugar cane spirits). The method involves the use of a flow injection (FI) preconcentration system and flame atomic absorption spectrometry (FAAS). The flow manifold was made up of four threeway solenoid valves, peristaltic pump and a minicolumn packed with the biosorbent obtained from tangerine peel Ponkan trated with NaOH. Middle Infrared Spectroscopy, Thermogravimetric Analysis and X-ray Diffraction were used to characterize the biosorbent. The point of zero charge of in natura tangerine peel and trated with NaOH were 4.8 and 6.0, respectively. Adsorption isotherms were used in order to identify the largest capacity of removal and the mechanisms involved between the material and the Ni(II). Multivariate methods were used (full factorial design 24 and response surface) for examine the best chemical and flow variables. The optimized conditions of the preconcentration system were: sample flow rate 4.27 mL min-1, eluent concentration of 1.0 mol L-1, biosorbent mass to 48.22 mg and sample initial pH 6.0. Test of homogeneity and stability (40 preconcentration/elution cycles) of the biosorbent used in the proposed method, as well evaluating the linear range (10.3 - 75 μg L-1), precision (R.S.D. de 0.90%), enrichment factor (11.783), sampling frequency (15 samples h-1), efficiency of concentration (3.1008 min-1), consumption index (0.85 ml), detection limits (3.1 μg L-1) and quantification (10.3 μg L-1) were performed to assess the analytical performance. The proposed methodology was applied in alcohol fuel samples, sugar cane spirits and whisky were found recovery to 99 - 110%.